1994
DOI: 10.1159/000168697
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antineutrophil Cytoplasmic Autoantibodies in Diagnosing Vasculitis in a Chinese Patient Population

Abstract: Antineutrophil cytoplasmic autoantibodies (ANCA) have been used as markers of systemic vasculitides, including microscopic polyarteritis (MPA) and Wegener’s granulomatosis. The diagnostic potential of ANCA assays together with antibodies against the neutrophil enzymes myeloperoxidase (MPO) and proteinase 3 for detecting a systemic vasculitis was tested in a Chinese patient population. 672 sera were received for ANCA assay, and ANCA detected by indirect immunofluorescence was positive in 73 sera from 42 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…The second concerned antigenic predominance. MPO and PR3 are the two major ANCA antigens for Chinese patients with AASV; however, the prevalence of P-ANCA/MPO-ANCA was much higher than that of C-ANCA/PR3-ANCA, with a ratio of 7:1, a finding that agreed with reports from Hong Kong (5,6). Limited observations suggest that the ANCA-associated disease process in northern latitudes more often produces the phenotype of Wegener's granulomatosis, while the phenotypic expression in warmer climates is more often that of microscopic polyangiitis and idiopathic pauci-immune necrotizing glomerulonephritis (14).…”
Section: Discussionsupporting
confidence: 87%
“…The second concerned antigenic predominance. MPO and PR3 are the two major ANCA antigens for Chinese patients with AASV; however, the prevalence of P-ANCA/MPO-ANCA was much higher than that of C-ANCA/PR3-ANCA, with a ratio of 7:1, a finding that agreed with reports from Hong Kong (5,6). Limited observations suggest that the ANCA-associated disease process in northern latitudes more often produces the phenotype of Wegener's granulomatosis, while the phenotypic expression in warmer climates is more often that of microscopic polyangiitis and idiopathic pauci-immune necrotizing glomerulonephritis (14).…”
Section: Discussionsupporting
confidence: 87%
“…Some previous studies of white populations have noted a predominance of males while the Chinese study reported an equal number of males and females of all ages, predominance of females in those 20 years of age and under (females:males; ratio 4:1). Similar findings have been reported from Hong Kong (MPO:PR3; 7:1) [17,18].…”
Section: Classification and Epidemiologysupporting
confidence: 89%
“…Although a positive perinuclear accentuated ANCA (p-ANCA) is common in inflammatory bowel disease, a positive c-ANCA is not. [5][6][7][8] We now describe a patient with ulcerative colitis (UC) who presented with noninfectious peripheral pulmonary infiltrates, a persistently elevated c-ANCA, and pulmonary symptoms mimicking WG who was later diagnosed as hav¬ ing sulfasalazine pulmonary toxicity.…”
mentioning
confidence: 99%